Indonesia Economic Quarterly, March 2013 : Pressures Mounting - World Bank (Washington, DC, 2014)
Indonesia's economy continued to grow at a steady pace in the final quarter of 2012, taking full-year GDP growth to 6.2 percent. This was only a modest reduction from the 6.5 percent growth recorded in 2011, a resilient performance considering the weak global environment and unsettled financial market conditions which prevailed for much of the year. Looking ahead, Indonesia should be able to maintain a solid pace of growth, but there is no room for complacency, as a number of pressures are mounting which could move the economy off this trajectory. Global economic uncertainties remain elevated, Indonesia s investment growth has moderated and, as highlighted in the December 2012 IEQ, the quality of domestic policies is increasingly in focus, particularly in the run-up to the 2014 elections. Even if growth of 6.0 to 6.5 percent is maintained, there is a risk that, without more progress on policy reform and implementation, the opportunity could be missed to boost growth at a time when the economy is benefiting from a growing labor force and the agglomeration effects of urbanization. Future appointments to key economic policy roles, following the nomination of the Minister of Finance as the next Governor of Bank Indonesia (BI), will also frame the macroeconomic policy environment going forward. The final quarter of 2012 remained challenging for many of Indonesia s major trading partners; growth in the US and Japan was flat and the Euro Area recession deepened, though growth in China firmed. Moving into 2013, global growth remains subdued but international economic conditions have turned somewhat more supportive for growth in Indonesia. Global industrial production is increasing at a modest pace, and global trade is expanding again, with broad-based increases for developing countries exports. Commodity prices have also generally posted modest gains since December, including those of some of Indonesia s key export products like copper, rubber and palm oil. The improved global economic data, and diminishing fears over the risks of extreme adverse scenarios in the Euro area, US and China, coupled with accommodative monetary policy in most high income economies, have been broadly supportive of financial markets. Global equity markets rallied in the final two months of 2012 and have generally held these gains, with some developed country equity indices at or near record highs in nominal terms. Emerging market sovereign credit spreads have widened so far in 2013 but still remain close to their tightest levels since the global financial crisis.